2013
DOI: 10.1007/s00405-013-2722-7
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on extracellular matrix production of vocal fold scar fibroblasts in rats

Abstract: Vocal fold (VF) fibroblasts are the central subject of interest in fibrogenesis and wound healing after VF injury. Scar fibroblasts (SF) exhibit an aberrant production of several extracellular matrix (ECM) components which lead either to VF fibrosis or scarless wound healing. This study aimed to investigate the role of age at the time of injury on ECM production of SF. This is designed as an animal study. VF injury was established unilaterally in eight male Sprague-Dawley rats [3 months of age (n = 4), 11 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Recent publications by our group showed that age is, among others, an important factor when dealing with VFF. The cultured scar VFF of younger animals produced significantly higher levels of HA, even 3 months after injury, compared to the unaffected contralateral side and to the cultured scar VFF of older animals . We observed the same phenomenon under external stimulation for which the cultured sVFF of younger animals responded stronger to HGF‐stimulation …”
Section: Discussionsupporting
confidence: 72%
“…Recent publications by our group showed that age is, among others, an important factor when dealing with VFF. The cultured scar VFF of younger animals produced significantly higher levels of HA, even 3 months after injury, compared to the unaffected contralateral side and to the cultured scar VFF of older animals . We observed the same phenomenon under external stimulation for which the cultured sVFF of younger animals responded stronger to HGF‐stimulation …”
Section: Discussionsupporting
confidence: 72%
“…Vocal fold fibroblasts provide structural support to the lamina propria by producing growth factors and matrix fibers . In the presence of vocal fold scar, fibroblasts exhibit an unbalanced production of ECM components, leading to fibrosis . The ability of myofibroblasts to generate contractile forces is due to accumulation of cytoplasm and cellular fibronectin, resulting from ECM reorganization .…”
Section: Discussionmentioning
confidence: 99%
“…1,16,17 In the presence of vocal fold scar, fibroblasts exhibit an unbalanced production of ECM components, leading to fibrosis. 18 The ability of myofibroblasts to generate contractile forces is due to accumulation of cytoplasm and cellular fibronectin, resulting from ECM reorganization. 19 Myofibroblasts that express a-SMA are considered to be activated contractile fibroblasts and primarily responsible for excessive ECM contraction deposition with scar.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the VF due to vocal overuse or surgical procedures modify the behaviour of VFF, which may result in numerous VF pathologies (e.g. polyps, Reinke’s edema, VF scars) [7]. The resulting deterioration of the voice (dysphonia) reduces quality of life, leads to social withdrawal and affects the ability to work (e.g.…”
Section: Introductionmentioning
confidence: 99%